Quinazolin‐4(3H)‐one‐Based Hydroxamic Acids: Design, Synthesis and Evaluation of Histone Deacetylase Inhibitory Effects and Cytotoxicity. Issue 4 (21st March 2019) - Hieu, Doan Thanh; Anh, Duong Tien; Hai, Pham‐The; Thuan, Nguyen Thi; Huong, Le‐Thi‐Thu; Park, Eun Jae; Young Ji, A.; Soon Kang, Jong; Phuong Dung, Phan Thi; Han, Sang‐Bae; Nam, Nguyen‐Hai
Abstract: The present article describes the synthesis and biological activity of various series of novel hydroxamic acids incorporating quinazolin‐4(3 H )‐ones as novel small molecules targeting histone deacetylases. Biological evaluation showed that these hydroxamic acids were potently cytotoxic against three human cancer cell lines (SW620, colon; PC‐3, prostate; NCI−H23, lung). Most compounds displayed superior cytotoxicity than SAHA (suberoylanilide hydroxamic acid, Vorinostat) in term of cytotoxicity. Especially, N ‐hydroxy‐7‐(7‐methyl‐4‐oxoquinazolin‐3(4 H )‐yl)heptanamide (5b ) and N ‐hydroxy‐7‐(6‐methyl‐4‐oxoquinazolin‐3(4 H )‐yl)heptanamide (5c ) (IC50 values, 0.10–0.16 μm ) were found to be approximately 30‐fold more cytotoxic than SAHA (IC50 values of 3.29–3.67 μm ). N ‐Hydroxy‐7‐(4‐oxoquinazolin‐3(4 H )‐yl)heptanamide (5a ; IC50 values of 0.21–0.38 μm ) was approximately 10‐ to 15‐fold more potent than SAHA in cytotoxicity assay. These compounds also showed comparable HDAC inhibition potency with IC50 values in sub‐micromolar ranges. Molecular docking experiments indicated that most compounds, as represented by 5b and 5c, strictly bound to HDAC2 at the active binding site with binding affinities much higher than that of SAHA. Abstract :